Thermal Emission analysis to predict damage in specimens of High Strength Concrete (Fracture and Structural Integrity, 2020)
In this paper thermal analysis was applied to determine the “Critical Stress” of concrete, different from its ultimate strength, able to produce the first damage in the structures under compressive loads. The Critical Stress can be thought as the stress able to produce the beginning of fatigue rupture within the material. Several specimens of high strength concrete were tested in order to define the incipient crack phenomena, also in internal part of the specimen not accessible by direct inspections, with the aid of infrared thermography. A finite element analysis completes the study and compares, for the same static loading conditions, the stress state with the experimental thermographic images. The final results show as the coupling of normal compressive test and the acquisition of the thermal images can be a useful aid to estimate a security stress value, indeed the Critical Stress, before the Ultimate Serviceability Limit (SLU) of the structure, defined as the maximum load condition before its failure.
Keywords: crack; critical stress; fem; infrared thermography